Vormundschaftsgericht und Pflegekindschaft : die richterliche Regulation von Pflegekindschaftsverhältnissen und ihre Verknüpfung mit dem jugendamtlichen Verfahren - Hoch, Hans (My University, 1997)
The main question of this study is: How do the courts interpret the law, i.e., how are custody disputes handled in practice? In this study, the findings of 9 inter-views with experts (judges dealing with this special law) in the federal states of Baden-Württemberg, North-Rhine Westphalia, Bremen und Saxony are pre-sented.
The findings show the close connection and interdependence of administrative proceedings between welfare offices and courts. After a welfare office appeals to the courts in an effort to have children removed from the custody of their biologi-cal parents, the courts have three options: In response to the petition of the welfare office, the judges may regulate the proceedings in an (1) "affirmative", (2) "mediatorial" or (3) "corrective" (remedial) way.
Guardianship court and foster children
Keywords: guardianship court; fosterling; fosterfamiliy; guardianship; 900; Familie; Pflegekindschaft; Vormundschaft